Functional analysis of conserved non-coding regions around the short stature hox gene (shox) in whole zebrafish embryos. - Emma J Kenyon; Gayle K McEwen; Heather Callaway; Greg Elgar (PLoS ONE)
Background Mutations in the SHOX gene are responsible for Leri-Weill Dyschondrosteosis, a disorder characterised by mesomelic limb shortening. Recent investigations into regulatory elements surrounding SHOX have shown that deletions of conserved non-coding elements (CNEs) downstream of the SHOX gene produce a phenotype indistinguishable from Leri-Weill Dyschondrosteosis. As this gene is not found in rodents, we used zebrafish as a model to characterise the expression pattern of the shox gene across the whole embryo and characterise the enhancer domains of different CNEs associated with this gene. Methodology/principal findings Expression of the shox gene in zebrafish was identified using in situ hybridization, with embryos showing expression in the blood, putative heart, hatching gland, brain pharyngeal arch, olfactory epithelium, and fin bud apical ectodermal ridge. By identifying sequences showing 65% identity over at least 40 nucleotides between Fugu, human, dog and opossum we uncovered 35 CNEs around the shox gene. These CNEs were compared with CNEs previously discovered by Sabherwal et al., resulting in the identification of smaller more deeply conserved sub-sequence. Sabherwal et al.'s CNEs were assayed for regulatory function in whole zebrafish embryos resulting in the identification of additional tissues under the regulatory control of these CNEs. Conclusion/significance Our results using whole zebrafish embryos have provided a more comprehensive picture of the expression pattern of the shox gene, and a better understanding of its regulation via deeply conserved noncoding elements. In particular, we identify additional tissues under the regulatory control of previously identified SHOX CNEs. We also demonstrate the importance of these CNEs in evolution by identifying duplicated shox CNEs and more deeply conserved sub-sequences within already identified CNEs.